Determination of N-linked glycosylation in viral glycoproteins by negative ion mass spectrometry and ion mobility - Bitto, David (Methods Mol Biol, 2015)
Glycan analysis of virion-derived glycoproteins is challenging due to the difficulties in glycoprotein isolation and low sample abundance. Here, we describe how ion mobility mass spectrometry can be used to obtain spectra from virion samples. We also describe how negative ion fragmentation of glycans can be used to probe structural features of virion glycans.